2020
DOI: 10.3390/su12051992
|View full text |Cite
|
Sign up to set email alerts
|

Firm Characteristics and Corporate Social Responsibility: The Case of Czech Transportation and Storage Industry

Abstract: Nowadays, corporate social responsibility is an important factor in sustainable growth. The paper aims to examine the relationship between selected characteristics of firms (firm age, firm size, firm performance, and gender diversity of boards) and the application of a corporate social responsibility concept in the Czech transportation and storage industry. Using the data from own survey, the Albertina database, and the Business Register, and applying the Pearson and Spearman correlation coefficients and regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 43 publications
(53 reference statements)
6
43
0
4
Order By: Relevance
“…The main initiatives undertaken in this regard mainly concern corporate social responsibility (CSR) [5], green supply chain management [6] and eco-design [7]. The concept of Corporate Social Responsibility (CSR) is not easy to define, as it is a constantly evolving phenomenon [8]. The most shared definition of CSR concerns the integration of social, ethical, environmental, and philanthropic aspects in the company s activity and, more generally, in the company strategy [9].…”
Section: Introductionmentioning
confidence: 99%
“…The main initiatives undertaken in this regard mainly concern corporate social responsibility (CSR) [5], green supply chain management [6] and eco-design [7]. The concept of Corporate Social Responsibility (CSR) is not easy to define, as it is a constantly evolving phenomenon [8]. The most shared definition of CSR concerns the integration of social, ethical, environmental, and philanthropic aspects in the company s activity and, more generally, in the company strategy [9].…”
Section: Introductionmentioning
confidence: 99%
“…A research carried out by Madueño et al (2016) Orlitzky, Schmidt, and Rynes (2003), the core part of this theory is that CSR may be an organizational tool which might ensure a more effective use of resources, which in turn has a positive effect on the financial performance of the business. To summarize, there are many scholars who investigated the relationship between CRS and the corporate financial performance, and the consensus among them is that this relationship is positive (Činčalová & Hedija, 2020;Madueño et al, 2016;Perrini, Russo, Tencati, & Vurro, 2011). On the contrary, regarding the relationship of the CSR and the innovation performance, there is a lack of knowledge, and the connection is not fully established (Bocquet, Le Bas, Mothe, & Poussing, 2017, 2019Martinez-Conesa et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many previous studies have found that CSR functions as a strategic resource to facilitate competitive advantages in companies [ 6 , 7 , 8 ]. For example, CSR increases a variety of dimensions of organizational effectiveness, including customer evaluations of the firm and its products, corporate reputation, employees’ positive reactions, and financial performance [ 4 , 6 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%